FACTORS RELATING OF POSTPARTUM DEPRESSION IN INDEPENDENT PRACTICES OF MIDWIFE MISNI HERAWATI, HUSNIYATI AND SORAYA - Inge Anggi Anggarini (Universitas Muhammadiyah Semarang, 2019)
The postpartum period is a time when various changes, it occurs with women after childbirth, such as physiological, psychological, and socio-cultural and spiritual changes. Complex physical and emotional changes require adaptation to adjust lifestyle after labor and the new role of women to become mothers. It is also the originator of various psychological reactions, ranging from mild emotional reactions to severe levels of mental disorders. This study aims to determine the relationship between age, parity, education level, social support and physical exercise against postpartum depression. The design of this study is a descriptive correlative research type with a cross sectional approach. The number of samples was 32 respondents using concecutive sampling technique. Data collection using questionnaires and data analysis using chi-square. The results showed no significant relationship between age, parity, education level of postpartum depression. (p value> 0.05) and for social support and physical exercise factors during pregnancy there was a significant relationship with postpartum depression (p value <0.05). Keywords : Age, parity, social support, physical exercise during pregnancy, postpartum depression